Analisis Penggunaan Cement Deep Mixing (CDM) pada Proyek Proving Ground BPLJSKB Kabupaten Bekasi : Studi Kasus Zona High Speed Oval STA 2+840 – 2+980 - Muhammad Zuhdi; Rahmat Subriyanto; Lili Jamali; Moh Haifan (Lembaga Pengembangan Kinerja Dosen, 2026)
The Proving Ground Project of BPLJSKB Bekasi is a strategic infrastructure development aimed at improving vehicle quality, safety, and performance. The main challenges in this project is the low bearing capacity of the subsoil, particularly in the High Speed Oval zone at STA 2+840–2+980, which may lead to excessive settlement and structural instability. To address this issue, a soil improvement technique using Cement Deep Mixing (CDM) was implemented. This study aims to evaluate the effectiveness of CDM in enhancing soil strength and stability in the specified zone. A case study approach was employed by collecting primary and secondary data, including geotechnical investigation data, construction records, and laboratory and field test results before and after CDM implementation. The results indicate that the application of CDM significantly improves soil strength parameters, with an average increase of approximately 30% compared to the initial condition. In addition, CDM effectively reduces potential ground settlement and enhances slope stability in the project area. These findings demonstrate that Cement Deep Mixing is a reliable and sustainable ground improvement method for infrastructure projects constructed on soft soils. Therefore, CDM is recommended for similar projects requiring high structural performance and long-term stability.